(untitled) (Oratio Directa, 2024)
This study reviews the use of anthropomorphic techniques in the animation industry. Through qualitative research based on descriptive-interpretive analysis, a phenomenological approach, and the theory of anthropomorphism developed by Wells and Parkinson, the study finds that anthropomorphized animals in animation series and digital feature films generally retain their natural characteristics and behavior while being represented in human form. Animation products contribute to the reformulation of imagination and the formation of a positive human self-image because their stories relate to current issues in human life. Anthropomorphism is not only entertaining but also conveys moral values and creates emotional bonds between audiences and characters. The study encourages animation and creative-film producers to continue creating content relevant to increasingly complex audience demands.